A new binder on palm oil waste for polymer engineering product - Supri, Abdul Ghani, Prof. Madya Dr.; Salmah, Husseinsyah, Prof. Madya Dr.; Tan, Soo Jin; Mohammed Izzuddeen, Mohd Yazid (Korea Invention News, 2013)
The team has won gold medal at Cyber International Genius Inventor Fair (CIGIF) 2012, 3rd - 9th November 2012 was held at ChungMu Art Hall Convention Centre, Seoul, Korea.